Pemetaan Kompetensi Dasar IPA dan Agama: Langkah Awal Mewujudkan Pembelajaran IPA Terintegrasi Nilai Islam - Nining Purwati; Siti Zubaidah; Susriyati Mahanal (Universitas Negeri Jakarta, 2023)
Appropriate steps are needed to integrate religious subjects (Qur'an Hadith, Aqidah Akhlak, and Fiqh) so that integrated science learning of Islamic values ​​can be conducted successfully and adequately. One of the ways to make it successful is by mapping Basic Competencies in science subjects and religious subjects as the first step in this integration. A study has been carried out on Basic Competencies in science and religion subjects at Madrasah Tsanawiyah (MTs) with the aim of producing a map of the relevance of the Basic Competencies in these subjects. This study is a literature study that uses data sources in the form of 2013 curriculum documents, science and religion textbooks and related articles. The instruments in this study were researchers equipped with identification and data recording formats. Data was collected utilizing document study approaches, namely by analyzing the relevancy of each basic competency topic, which includes choosing references and identifying and classifying basic competencies. Data analysis was done qualitatively by classifying, summarizing, and deriving conclusions from the data. As a result of this research, a map of the correlation between scientific and religion basic competencies has been found. It demonstrates how one science basic competency in one class can be related to several fundamental religious competencies at all grade levels. This linkage provides a recommendation that science subject matter can be integrated with religion subject matter at all grade levels while still considering the linkages between these Basic Competencies.